Detecting and quantifying influenza virus with self‐ versus investigator‐collected mid‐turbinate nasal swabs. Issue 7 (27th February 2017) - Granados, Andrea; Quach, Susan; McGeer, Allison; Gubbay, Jonathan B.; Kwong, Jeffrey C.
Abstract : We compared pairs of self‐ and investigator‐collected mid‐turbinate nasal swabs to detect and quantify influenza viral loads. We used RNase P, which reflects presence of human cells to determine adequate sample collection. Sixteen pairs of influenza‐positive swabs and 25 pairs of influenza‐negative swabs were included in this study. The median influenza A viral loads for self‐ and investigator‐collected swabs were 1.68 and 1.67 log10 copies/mL, respectively ( P  = 0.96). RNase P loads were also similar between self‐ and investigator‐collected swabs ( P  = 0.51). Self‐collected mid‐turbinate nasal swabs yield comparable viral loads to investigator‐collected swabs, and therefore might be considered for research and clinical management.